(untitled) (Revista Espinhaço, 2015)
The urban landscape is shaped by the dynamics of society. Their characteristics leave records in space that may remain important impressions. Moreover, using the metaphor of the urban palimpsest as a reference, this work brings a historical assessment of the adulteration process of Belo Horizonte transport infrastructure, with the replacement of rail transportation for other attributes of the urban fabric. The study presents an evaluation of mesh railing territory of Belo Horizonte at two different times, based on spatial analysis tools and through two distinct types of documentary records: the IBGE topographic maps at 1:50,000 from 1960 to 1980 and recent satellite images provided by Google Earth software.